Modeling of stress-strain state and strength-element analysis of construction of inertial-filter gas tank - Мустафа, Аль-Раммахи Макки Мохаммед Али (Technology audit and production reserves, 2013)
The estimation of strength and stability of a device is an important task at the development stage of any new equipment, which is an inertial-filter gas tank. The purpose of the article is to study the structural strength of the tank with the help of modern computer modeling. For the experiment the module APM FEM made by "ASCON" was selected, which permits to recalculate automatically the stress-strain state when changing the geometry of a three-dimensional solid model. We have calculated the distribution of equivalent stresses and their components, as well as the principal stresses; the distribution of linear, angular and total displacements; the distribution of strains on the model elements; diagrams of the distribution of internal forces; the value of the coefficient of the stability factor and form of stability loss; the distribution of safety factors and the number of cycles according to the criterion of fatigue strength. The strength analysis of the module APM FEM helps solve linear problems of the stress-strain state (static analysis), static strength of assembly, stability, thermoelasticity, and stationary heat conductivity. The dynamic analysis permits to determine the frequencies and forms of the natural oscillations, including models with a pre-load.